2004
DOI: 10.1002/ts.140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of auxins on root development in yam (Dioscorea rotundata) vine

Abstract: Treatment with indolebutyric acid (IBA) significantly increased the number of roots produced by vine cuttings of ten Dioscorea rotundata cultivars. Some cultivars could be propagated by layering, especially with IBA treatment, but layering does not appear to be feasible for use on farms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 4 publications
(1 reference statement)
1
15
1
1
Order By: Relevance
“…Rooted vine cuttings at 20cm long and with 1 to 3-nodes [14][15][16] produced mini-tubers of 50-600g after 8 months giving a 1:30 propagation ratio. Other high propagation ratio technologies exist but are not being used for yam [17].…”
Section: Introductionmentioning
confidence: 99%
“…Rooted vine cuttings at 20cm long and with 1 to 3-nodes [14][15][16] produced mini-tubers of 50-600g after 8 months giving a 1:30 propagation ratio. Other high propagation ratio technologies exist but are not being used for yam [17].…”
Section: Introductionmentioning
confidence: 99%
“…While varietal differences in the rooting of vines have been noted, Acha et al (2004) observed significant increase in the number of roots after treatment with indolebutyric acid. Cabanillas and Martin (1978) noted that using single node cuttings, multiplication of yams could be several hundred fold in 1 year.…”
Section: Modern Methods Of Seed Yam Productionmentioning
confidence: 90%
“…Rooted vine cuttings of 20 cm length with 1 to 3-nodes (Acha et al 2004;Kikuno et al 2007;Agele et al 2010) produced mini-tubers of 50-600 g after 8 months giving a 1:30 propagation ratio. Vine cuttings for tuber production should be taken from healthy plants aged between 30 and 60 days after shoot emergence, and before tuber development starts (Okonmah 1980;Kikuno et al 2007).…”
Section: Modern Methods Of Seed Yam Productionmentioning
confidence: 99%
“…More recently, rooting of 20 cm long 3-node vines (Acha et al, 2004;Kikuno et al, 2007;Agele et al, 2010) produced minitubers of 50 to 600 g after 8 months giving a 1:22 propagation ratio.…”
Section: Existing Seed Yam Production Systemmentioning
confidence: 99%
“…The layering of vines into soil for tuber production while on the mother plant is unpractical for farm use although up to 1:80 propagation ratio is possible (Acha et al, 2004). All of these macropropagation techniques are genotype-dependent, have no provision for cleaning infected seed yam and tuber dormancy remains a challenge.…”
Section: Existing Seed Yam Production Systemmentioning
confidence: 99%